The Impact of Exchange Rate Policy and Exchange Rate Volatility on Exports: A Case Study of Türkiye (Third Sector Social Economic Review, 2025)
Exports play a crucial role in shaping key macroeconomic indicators of the Turkish economy, such as growth, employment, and the current account balance. In this context, understanding the impact of exchange rate policies and exchange rate volatility on exports holds strategic importance for both policymakers and exporters. This study investigates the effects of exchange rates and their volatility on Türkiye's export performance over the period 2002:Q1–2023:Q2 using a Time-Varying Parameter (TVP) regression model. In the model, exports are used as the dependent variable, while the weighted average GDP of Türkiye’s top five export destinations in Europe, the exchange rate (average of USD and Euro), and exchange rate volatility calculated via the GARCH(1,1) model serve as independent variables. Empirical findings indicate that while the exchange rate has a generally positive effect on exports, exchange rate volatility weakens this impact. In particular, the adverse effects of volatility on exports become more prominent during the 2009 global financial crisis, the Covid-19 pandemic, and the post-2021 New Economic Model period. The results highlight that exchange rate stability is critical for export performance, and that in export-oriented growth strategies, not only the level of the exchange rate but also its volatility dynamics must be taken into account.
Keywords: Exchange Rate Volatility; Export Performance; Time-Varying Parameters (TVP); Turkish Economy; GARCH Model